ANALISIS POTENSI ADMIXTURE JENIS PLASTISIZER ALAMI SEBAGAI BAHAN TAMBAH BETON TIPE SELF COMPACTING CONCRETE (SCC): ANALISIS POTENSI ADMIXTURE JENIS PLASTISIZER ALAMI SEBAGAI BAHAN TAMBAH BETON TIPE SELF COMPACTING CONCRETE (SCC) - Wicaksono, Teguh Mulyo; Mukhlisin, Muhammad; Fatmawati, Leily; Rahmawati, Roselina (Politeknik Negeri Semarang, 2025)
Self-compacting concrete (SCC) is a type of concrete that has the ability to flow and consolidate itself without the need for vibration. The addictive substance for self-compacting concrete uses chemical plasticizers produced by concrete chemical companies. The nature of the plasticizer material is usually liquid and thick which is used to thin the mixture and increase the workability of the concrete. The research began by creating a mix design including preparation of the need for natural additives. Testing the thinness of the concrete mix can be carried out using a flow test or fresh concrete spread test, where SCC meton meets the criteria if it gets a minimum spread test diameter of 50 cm. Some natural materials that are thick in nature include aloe vera sap, egg white, snail mucus and others. Tests using plasticizer fabricated products from Sika Viscocrete 3000 had the highest Flow values ​​for SCC concrete, followed by Sugar Solution, Allovera, Egg White and Snail Liquid. The results of successive cylindrical concrete compression tests produced average strengths ranging from Sika Viscocrete 23.6 Mpa, Allovera 14.23 Mpa, Snail 13.75 Mpa, Egg White 11.0 Mpa, and Sugar 3.1 Mpa. Fabricated plasticizers have very good results as additional materials for Self Compacting Concrete type concrete, while the natural material that still has potential in terms of flow is sugar solution, while in terms of compressive strength it is allovera.